2021
DOI: 10.7717/peerj.11699
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pathogen(s) in infectious diseases using shotgun metagenomic sequencing and conventional culture: a comparative study

Abstract: Background Early and accurate diagnosis of microorganism(s) is important to optimize antimicrobial therapy. Shotgun metagenomic sequencing technology, an unbiased and comprehensive method for pathogen identification, seems to potentially assist or even replace conventional microbiological methodology in the diagnosis of infectious diseases. However, evidence in clinical application of this platform is relatively limited. Methods To evaluate the capability of shotgun metagenomic sequencing technology in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The antimicrobial agents more commonly used were vancomycin in 68.4% (26 out of 38 patients), cephalosporins in 28.9% (11), aminoglycosides in 26.3% (10), the combination of trimethoprim with sulfamethoxazole in 21.1% (8), rifampicin in 15.8% (6), carbapenems in 13.2% (5), penicillin in 10.5% (4), aminopenicillins in 10.5% (4), linezolid in 10.5% (4), clindamycin in 7.9% (3), macrolides in 7.9% (3), and quinolones in 7.9% (3). The median treatment duration among survivors was 21.5 days, ranging from 7 to 264 days, with an interquartile range of 14 to 57.8 days.…”
Section: Treatment and Outcomes Of Cellulosimicrobium Species Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial agents more commonly used were vancomycin in 68.4% (26 out of 38 patients), cephalosporins in 28.9% (11), aminoglycosides in 26.3% (10), the combination of trimethoprim with sulfamethoxazole in 21.1% (8), rifampicin in 15.8% (6), carbapenems in 13.2% (5), penicillin in 10.5% (4), aminopenicillins in 10.5% (4), linezolid in 10.5% (4), clindamycin in 7.9% (3), macrolides in 7.9% (3), and quinolones in 7.9% (3). The median treatment duration among survivors was 21.5 days, ranging from 7 to 264 days, with an interquartile range of 14 to 57.8 days.…”
Section: Treatment and Outcomes Of Cellulosimicrobium Species Infectionsmentioning
confidence: 99%
“…These new diagnostic modalities have led to the accurate and more frequent identification of relatively rare microorganisms [ 1 , 2 ]. Such microorganisms may have been very difficult identify with classical microbiological tools that assess the morphology and biochemical profile of these microorganisms [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This untargeted sequencing approach leads to the generation of taxonomic information from conserved genes, such as the 16S rRNA gene, as well as a complete overview of the panoply of genomes present, including information on virulence, antimicrobial resistance and metabolic potential [69]. Theoretically, the identification of pathogens and antimicrobial susceptibility testing (AST) could be determined using the same test [69,150]. Barraud et al demonstrated this by using shotgun metagenomics to correctly profile bacteria in urine samples from sepsis patients, while also detecting antimicrobial resistance (AMR) genes that corresponded with standard AST results [151].…”
Section: Shotgun Metagenomics To Study the Microbial Metagenomementioning
confidence: 99%
“…The identification of novel microorganisms has become more frequent in the current era, where genetic methods such as 16S rRNA gene sequencing have been implemented [ 1 , 2 ]. These methods have the potential to more accurately diagnose infections by microorganisms that are harder to identify by classic microbiological means [ 3 ].…”
Section: Introductionmentioning
confidence: 99%